Develop a Quality Control System to Build Integrated Engineering Characteristics in the Civil Engineering Students - Ahmed Gaber Abdelhamid Ahmed; R. Madhakomala (Jurnal Pendidikan dan Kebudayaan Nusantara, 2025)
Objective: many of researches mentioned that the graduated from civil engineering faculty has an in-complete engineering characteristic; despite the faculty curriculum is designed as competency-based approach, this study aim to explore this gap and give suggested solutions, as the required competencies is already is fixed as a goals of the curriculum to be achieved, but there are lack of implementation due to un-achieved goals. Method: qualitative method using literature review to extract the gap and to be able to solve it.  Results:  after collecting the data, it will be grouped into different similar contexts to build the understanding, and then produce the result as a procedure consistent with logic steps. Novelty: bridging the gap between the competency-based curriculum and the incomplete engineering characteristic through the implementation and evaluation of a solution.